KEBO LEAF ETHANOL EXTRACT (Euphorbia hirta L.) ANTI-INFLAMMATORY EFFECTS IN FEMALE WHITE RATS DETERMINED USING ARTIFICIAL UDEMA METHOD - Mevy Trisna; Renatalia Fika; Budi Setiawan; Rini Wulandari (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
An ordinary protective reaction to tissue damage brought on by physical trauma, chemical agents, or harmful microbiological agents is inflammation. The kebo excerpt plant has significant amounts of flavonoids, which have anti-inflammatory and antioxidant properties. This study used the artificial udema method to determine the anti-inflammatory effects of Kebo Petikan leaves (Euphorbia hirta L.) ethanol extract in female white rats. This study applied a subcutaneous 1% carrageenine inducer as an anti-inflammatory drug on the soles of rats' feet. Following the injection of the test material at doses of 26 mg, 52 mg, and 104 mg, a decrease in volume was the metric that was observed. The results of the study showed the anti-inflammatory effect of ethanol extract of kebo petikan leaves at a dose of 26 mg/5ml had a strength of 32.3%, a dose of 52 mg/5ml had a strength of 78.48 %, and a dose of 104 mg/5ml had a strength of 91.46% compared to drugs.